Analisis Strategi Penguatan Kelembagaan Masyarakat Dalam Program Rehabilitasi Hutan dan Lahan (RHL) di Desa Sumberejo, Kabupaten Wonogiri, Wilayah Kerja BPDAS Solo - Mita Nur Hidayati; Aziz Akbar Mukasyaf; Danardono; Afif Ari Wibowo (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The success of the Forest and Land Rehabilitation (RHL) Program is influenced by the level of community participation and institutional capacity at each stage of implementation. This study aims to analyze the level of community institutional participation, identify internal and external factors affecting these institutions, and formulate strategies to strengthen community institutions within the RHL Program in Sumberejo Village, Wonogiri Regency (under the jurisdiction of BPDAS Solo). A descriptive approach employing both quantitative and qualitative methods was used. Data were collected through observation, interviews, questionnaires, and document review involving 40 members of the Forest Farmer Group selected via random sampling, while key informants were chosen through purposive sampling. Data analysis utilized a Likert scale, IFAS-EFAS matrices, and SWOT analysis. The results indicate that community institutional participation falls into the "high" category during the implementation (79.37%) and output utilization (81.37%) stages, whereas the planning (63.12%) and evaluation (54.75%) stages fall into the "moderate" category. Identification results reveal that member engagement, group cooperation, and group leadership are key strengths, while limited knowledge regarding rehabilitation and group management remains a weakness. Externally, government support, facilitation, and the availability of rehabilitation land represent major opportunities, despite challenges posed by unpredictable weather and pest infestations. These conditions place the community institutions in Quadrant I; consequently, an SO (Strengths-Opportunities) strategy is prioritized to bolster participation, group cooperation, and the utilization of government support, thereby ensuring the sustainability of the RHL Program.